Primitive homochiral polyester formation driven by tartaric acid and calcium availability - Chen Chen; Ruiqin Yi; Motoko Igisu; Rehana Afrin; Mahendran Sithamparam; Kuhan Chandru; Yuichiro Ueno; Linhao Sun; Tommaso Laurenzi; Ivano Eberini; Tommaso P. Fraccia; Anna Wang; et al. (Proceedings of the National Academy of Sciences, 2025)
α-hydroxy acids (αHAs), simple and prebiotically plausible organic monomers, were likely present in various environments on and off Earth and could have played a role in directing the emergence of the first homochiral living systems. Some αHAs, which could have been of varying chirality, can undergo dehydration polymerization into polyesters, which could assemble into membraneless microdroplets upon rehydration; understanding these processes is critical for unraveling how simple prebiotic molecules transitioned into more complex systems capable of supporting selective chemical reactions, a key step toward the origin of life. Here, we focused on tartaric acid (TA), a prebiotically relevant αHA with multiple chiral forms, to probe plausible mechanisms by which primitive αHA and polyester-based systems could have participated in selective homochiral polymer synthesis. Enantiopure solutions of d -TA or l -TA polymerize efficiently via dehydration, while racemic dl -TA polymerization is inhibited due to stereochemical incompatibility. We found that Ca 2+ ions influence this process in two significant ways: 1) regulating TA monomer availability through selective crystallization, removing equal amounts of both enantiomers in racemic proportion and thereby enriching the enantiomeric excess of the remaining nonracemic TA solution; and 2) modulating polymerization by suppressing enantiopure TA polymerization while enabling dl -TA polymerization. These findings suggest that the differential availability of simple inorganic ions, such as Ca 2+ , could have indirectly mediated the selection of simple organic chiral monomers and the emergence of homochirality in primitive protocell-forming polymers, offering a pathway from nonliving to living matter in early Earth environments.